Preferential and non-preferential trade flows in world trade - Jean-Marie Grether; Marcelo Olarreaga (World Trade Organization (WTO), 1998)
This paper quantifies the extent of preferential trade as a share of total world trade in different regions of the world and for two periods. Results show that: i) preferential trade represented 40% of world trade in the period 1988-1992 and it slightly increased to 42% during the period 1993-1997; ii) during the second period, agricultural products generally benefited more from the existence of preferential trade agreements than industrial products (maybe due to GATT-exemption); iii) the regional distribution of preferential trade is relatively uneven with a significant share of preferential trade in Western Europe (around 70 per cent), relatively low values in the Western Hemisphere (around 25 per cent), very low shares in Asia and Oceania (around 4 per cent) and average values in the rest-of-the-world (Eastern Europe and Africa); iv) the largest increase in shares of preferential trade between the two periods has occurred in the Western Hemisphere and in Eastern-Europe and Africa; v) at the country level there is an inverted-u-shape relationship between the share of preferential trade and the size and GDP per capita of individual countries; vi) countries which are highly open to trade tend to have a larger share of preferential trade on total trade in the period 1993-1997, suggesting that preferential and non-preferential trade can be seen as complements.
Keywords: F11; F12; 330; International trade; preferential trade agreements